Estimation of The Shelf Life of Wedang Uwuh Ready to Drink with Blanching and Non Blanching Treatments - Erika Amalia Putri; Safinta Nurindra Rahmadhia; Retnosyari Septiyani (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
Wedang uwuh developed into a ready-to-drink beverage which began to be produced commercially. Determination of shelf life needs to be done to determine the time span and provide quality assurance from the start of production until it is not acceptable to consumers. One of the factors that influence changes in quality is temperature. The main parameters used are pH and color which are considered to most affect the chemical and physical quality of a product. The purpose of this study was to determine changes in pH and color during storage and the shelf life of ready-to-drink Uwuh Wedang. The shelf life estimation method used is the Accelerated Shelf Life Testing (ASLT) Arrhenius approach with storage temperatures of 40°C, 50°C and 60°C thereby accelerating quality degradation. Observations every day - 0, 3, 6, 9, 12, and 15 with three repetitions. Color analysis uses two-way analysis of variance (ANOVA). The research data showed that the shelf life of wedang uwuh ready to drink blanching treatment sequentially at 40°C, 50°C, and 60°C was 18, 15, and 12 days. While wedang uwuh ready to drink non blanching sequentially, we have 10, 9, and 9 days. Storage temperature and time have a significant effect on the color change of ready-to-drink blanching and non-blanching wedang uwuh. Ready-to-drink Wedang Uwuh turns red to brownish orange and the color of Wedang Uwuh ready to drink from blanching treatment is brighter than non-blanching.Keywords - Quality, Temperature, Ready to Drink, Shelf Life, Wedang Uwuh.